Budget credibility of subnational governments: Analyzing the fiscal forecasting errors of 28 states in India - Lekha Chakraborty; Pinaki Chakraborty; Ruzel Shrestha (Levy Economics Institute of Bard College, 2020)
Budget credibility, or the ability of governments to accurately forecast macro-fiscal variables, is crucial for effective public finance management. Fiscal marksmanship analysis captures the extent of errors in the budgetary forecasting. The fiscal rules can determine fiscal marksmanship, as effective fiscal consolidation procedures affect the fiscal behavior of the states in conducting the budgetary forecasts. Against this backdrop, applying Theil's technique, we analyze the fiscal forecasting errors for 28 states (except Telangana) in India for the period 2011-16. There is a heterogeneity in the magnitude of errors across subnational governments in India. The forecast errors in revenue receipts have been greater than revenue expenditure. Within revenue receipts, the errors are more significantly pronounced in the grants component. Within expenditure budgets, the errors in capital spending are found to be greater than revenue spending in all the states. Partitioning the sources of errors, we identified that the errors were more broadly random than due to systematic bias, except for a few crucial macro-fiscal variables where improving the forecasting techniques can provide better estimates.
Keywords: H6; E62; C53; 330; Forecast Errors; Fiscal Policies; Fiscal Forecasting; Political Economy; Fiscal Marksmanship